Customary Marriage Between Custom and Law in Algeria A study theoretical - - Fatima SALMI; Hafsa DJERADI (Social Sciences Journal, 2018)
Marriage is the basis of family formation, which is a fundamental unit of society, and anyimbalance in this foundation will have a profound impact on both the family and the community.Marriage has changed in its types and forms due to the appearance of laws governing it, Amongthese phenomena is the prevalence of customary marriages, especially among young people in theArab world, we first explore the nature of the customary marriage and its legitimate rule, as well asits motives and effects in Algerian societ